Bioactivity and bioaccessibility of protein hydrolyzates from industrial byproducts of Stripped weakfish (Cynoscion guatucupa). (August 2019) - Lima, Karina Oliveira; da Costa de Quadros, Camila; Rocha, Meritaine da; Jocelino Gomes de Lacerda, José Thalles; Juliano, Maria Aparecida; Dias, Meriellen; Mendes, Maria Anita; Prentice, Carlos
Abstract: Protein hydrolyzates of Stripped weakfish ( Cynoscion guatucupa ) industrial byproducts were prepared, and their antimicrobial and antioxidant activities, as well as bioaccessibility were evaluated. Byproducts were hydrolyzed by Alcalase (HA) and Protamex (HP) to achieve degrees of hydrolysis (DH) of 5, 10 and 15%, respectively. Resulting hydrolyzates were enzymatically digested with pepsin and pancreatin to determine the in vitro bioaccessibility. The highest antimicrobial activity was verified for HA with DH 5% (HA5) against Escherichia coli O157:H7 (5.50 ± 0.17 mm). Whereas HP with DH 5% (HP5) showed the highest antioxidant activity for the tested assays. After simulated in vitro gastrointestinal digestion, all samples were bioaccessible and showed an increase for the ABTS and hydroxyl radical scavenging with the highest activities for HA5 (87.7 ± 0.21%) and HP5 (87.5 ± 0.34%) and HP5 (96.7 ± 0.86%) and HP15 (97.5 ± 0.15%), respectively. We then submitted HA5 and HP5 to peptide sequences analysis, the bioactivities were attributed to the presence of amino acid such Phe, Leu, and Trp in the peptide sequences and peptide sequences like WDDMEK (HP5). The developed peptides present a potential for use as natural antimicrobial and antioxidant preservatives in food. Highlights: Hydrolyzates of C. guatucupa byproducts were prepared using Alcalase and Protamex. Inhibition of E. coli and S. aureus growth by protein hydrolyzates with 5% DH. Hydrolyzates with 5% DH by Protamex showed higher antioxidant activity. The hydrolyzates were bioaccessible with antioxidant activity. Bioactivities were attributed to the presence of specific amino acids or fragments.